2014
DOI: 10.1371/journal.pone.0113623
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profile Analysis of Citrus Sucrose Synthase Genes: Investigation of Possible Roles in the Regulation of Sugar Accumulation

Abstract: Sucrose synthase (Sus) (EC 2.4.1.13) is a key enzyme for the sugar accumulation that is critical to form fruit quality. In this study, extensive data-mining and PCR amplification confirmed that there are at least six Sus genes (CitSus1-6) in the citrus genome. Gene structure and phylogeny analysis showed an evolutionary consistency with other plant species. The six Sus genes contain 12–15 exons and 11–14 introns and were evenly distributed into the three plant Sus groups (CitSus1 and CitSus2 in the Sus I group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…In general, three pivotal mechanisms contribute to gene family evolution and expansion: exon/intron gain or loss, exonization/pseudo-exonization, and insertion/deletion [17]. For the three groups in Figure 2, according to the phylogenetic relationships of five VvSS genes in the present study (see the contents below) and previous work in other plants [49,50], Group III ( VvSS1/VvSS5 ) was the earliest one that expanded from the evolutionary branch. As a result, VvSS1/VvSS5 has the longest evolutionary history, leading to the complex of intron/exon structure.…”
Section: Discussionmentioning
confidence: 80%
“…In general, three pivotal mechanisms contribute to gene family evolution and expansion: exon/intron gain or loss, exonization/pseudo-exonization, and insertion/deletion [17]. For the three groups in Figure 2, according to the phylogenetic relationships of five VvSS genes in the present study (see the contents below) and previous work in other plants [49,50], Group III ( VvSS1/VvSS5 ) was the earliest one that expanded from the evolutionary branch. As a result, VvSS1/VvSS5 has the longest evolutionary history, leading to the complex of intron/exon structure.…”
Section: Discussionmentioning
confidence: 80%
“…Sucrose synthase (Sus) (EC 2.4.1.13) is a key enzyme for sugar accumulation that catalyzes the reversible reaction of sucrose and UDP into UDP-glucose and fructose, whereas invertase hydrolyzes sucrose into glucose and fructose (Koch, 2004). During fruit development, there is an increase in CitSus5 transcript levels, being CitSus1, 2, 5 and 6 predominantly expressed in fruit juice sacs during ripening (Islam et al, 2014). Gene expression studies indicated that sucrose is synthetized in the juice sacs and that the balance between sucrose synthase/invertase play a key role in the regulation of sucrose content (Katz et al, 2011).…”
Section: Sugars and Acidsmentioning
confidence: 99%
“…The two steps of sucrose degradation and resynthesis favor the sucrose import by generating a sucrose concentration gradient in the sink local zone for phloem unloading [17]. A collection of genes encoding the enzymes for sucrose transport and metabolism have been reported, including three sucrose transporters (CitSUT1, CitSUT2, and CitSUT3) for sucrose loading or unloading [18], three sucrose synthase isoforms (CitSUS1/2 and CitSUSA) from Citrus unshiu [17], and six SS homologs from publicly available genome database for sweet orange and clementine (citrus.hzau.edu.cn/orange and www.phytozome.net) [19], and their transcriptional and translational expression patterns were investigated during citrus fruit development. Generally, the sucrose synthase activity and expression levels are relatively low at the citrus fruit immature stage favoring sucrose accumulation and increased during fruit development favoring improving sink strength and sucrose import, while different sucrose synthases showed their unique expression patterns [19,20].…”
Section: Sweetmentioning
confidence: 99%
“…A collection of genes encoding the enzymes for sucrose transport and metabolism have been reported, including three sucrose transporters (CitSUT1, CitSUT2, and CitSUT3) for sucrose loading or unloading [18], three sucrose synthase isoforms (CitSUS1/2 and CitSUSA) from Citrus unshiu [17], and six SS homologs from publicly available genome database for sweet orange and clementine (citrus.hzau.edu.cn/orange and www.phytozome.net) [19], and their transcriptional and translational expression patterns were investigated during citrus fruit development. Generally, the sucrose synthase activity and expression levels are relatively low at the citrus fruit immature stage favoring sucrose accumulation and increased during fruit development favoring improving sink strength and sucrose import, while different sucrose synthases showed their unique expression patterns [19,20]. Komatsu et al (2002) investigated the transcript levels of CitSUS1/2 and CitSUSA during citrus development and suggested that CitSUS1 may help provide the sucrose degradation products for growth and cell wall construction while CitSUSA plays more roles in providing substrates for sucrose resynthesis in concert with the function of SPS [17].…”
Section: Sweetmentioning
confidence: 99%